Tissue Inhibitor of Metalloproteinase-3 (TIMP-3) Regulates Hematopoiesis and Bone Formation In Vivo - Shen, Yi (Public Library of Science, 2010)
BACKGROUND: Tissue inhibitor of metalloproteinases-3 (TIMP-3) inhibits matrix metalloproteinases and membrane-bound sheddases. TIMP-3 is associated with the extracellular matrix and is expressed in highly remodeling tissues. TIMP-3 function in the hematopoietic system is unknown. METHODOLOGY/PRINCIPAL FINDINGS: We now report that TIMP-3 is highly expressed in the endosteal region of the bone marrow (BM), particularly by osteoblasts, endothelial and multipotent mesenchymal stromal cells which are all important cellular components of hematopoietic stem cell (HSC) niches, whereas its expression is very low in mature leukocytes and hematopoietic stem and progenitor cells. A possible role of TIMP-3 as an important niche component was further suggested by its down-regulation during granulocyte colony-stimulating factor-induced mobilization. To further investigate TIMP-3 function, mouse HSC were retrovirally transduced with human TIMP-3 and transplanted into lethally irradiated recipients. TIMP-3 overexpression resulted in decreased frequency of B and T lymphocytes and increased frequency of myeloid cells in blood and BM, increased Lineage-negative Sca-1(+)KIT(+) cell proliferation in vivo and in vitro and increased colony-forming cell trafficking to blood and spleen. Finally, over-expression of human TIMP-3 caused a late onset fatal osteosclerosis. CONCLUSIONS/SIGNIFICANCE: Our results suggest that TIMP-3 regulates HSC proliferation, differentiation and trafficking in vivo, as well as bone and bone turn-over, and that TIMP-3 is expressed by stromal cells forming HSC niches within the BM. Thus, TIMP-3 may be an important HSC niche component regulating both hematopoiesis and bone remodeling.